Serious games as a validation tool for PREDIS: a decision support system for disaster management - Rye, Sara; Aktas, Emel (MDPI, 2022)
In this paper, we validate PREDIS, a decision support system for disaster management using serious games to collect experts’ judgments on its performance. PREDIS is a model for DISaster response supplier selection (PREDIS). It has a PREDictive component (PRED) for predicting the disaster human impact and an estimation component to Estimate the DISaster (EDIS) needs to optimise supplier-based resource allocation. A quasi-experiment design embedded in a participatory simulation game is conducted to compare the opinions of equal samples of 22 experts and non-experts. The following questions are put forward. First, “Does PREDIS model assists the decision makers to make the same decisions faster?” Second, “Does the PREDIS model assist the non-experts as simulated decision makers to decide like an expert?” Using AHP weights of decision makers’ preferences as well as Borda counts, the decisions are compared. The result shows that PREDIS helps to reduce the decision-making time by experts and non-experts to 6 h after the disaster strike, instead of the usual 72 h. It also assists 71% of the non-experts to make decisions similar to those made by experts. In summary, the PREDIS model has two major capabilities. It enables the experts and non-experts to predict the disaster results immediately using widely available data. It also enables the non-experts to decide almost the same as the experts; either in predicting the human impact of a disaster and estimating the needs or in selecting suitable suppliers.
Keywords: decision-making; disaster response; DSS; simulation game; proliferation of suppliers; serious game